PENGARUH MATA KULIAH SOLFEGIO TERHADAP KEMAMPUAN TRANSKRIPSI MAHASISWA JURUSAN SENDRATASIK FBS UNP ANGKATAN 2015 - Nanda Hidayat Nanda Hidayat; Jagar Lumbantoruan; Irdhan Epria Darma Putra (SENDRATASIK UNP, 2018)
AbstrakThe first data, through analysis of study result of Departement of Arts, Drama, Dance and Music 2015 students on Solfegio and music transcription Subject, it could be seen that there were some cases in relathionship between both of them, namely the last semester students who took line of work, they have the same problem, that was difficulty in transcripting music. Type of this study was quantitative, the method which was based on positivism. It was used to research on population or specific sample. Technique of data collection were done randomly by using instrument. Data analysis was quantitatively / statistic with purpose to test hypothesis which had been stated. (Sugiyono, 2006:14). Population in this study were Departement of Arts, Drama, Dance and Music 2015 students at class transcription and music analysis. In this study, data gained by taking documentation of student study result on solfegio and transcription subjects. Then, data were analyzed by using test of cofesion and correlation. Based on data analysis, it could be seen that corelation value was 22,845%. This value was in underweight category. It meant that the lack of cometence influence which was gained by Departement of Arts, Drama, Dance and Music 2015 students terhadap solfegio and transcription subjects. This competence was improved more  because this had great effect toward the ability of students in transcripting or writing music. Keywords : Solfegio, Transcription, Effect.